Neon in ultrashort and intense x-rays from free electron lasers - Buth, Christian; Beerwerth, Randolf; Obaid, Razib; Berrah, Nora; Cederbaum, Lorenz S.; Fritzsche, Stephan (Journal of physics. B, Atomic, molecular and optical physics, 2018)
We theoretically examine neon atoms in ultrashort and intense x-rays from free electron lasers and compare our results with data from experiments conducted at the Linac Coherent Light Source. For this purpose, we treat in detail the electronic structure in all possible nonrelativistic cationic configurations using a relativistic multiconfiguration approach. The interaction with the x-rays is described in rate-equation approximation. To understand the mechanisms of the interaction, a path analysis is devised which allows us to investigate what sequences of photoionization and decay processes lead to a specific configuration and with what probability. Thereby, we uncover a connection to the mathematics of graph theory and formal languages. In detail, we study the ion yields and find that plain rate equations do not provide a satisfactory description. We need to extend the rate equations for neon to incorporate double Auger decay of a K-shell vacancy and photoionization shake off for neutral neon. Shake off is included for valence and core ionization; the former has hitherto been overlooked but has important consequences for the ion yields from an x-ray energy below the core ionization threshold. Furthermore, we predict the photon yields from xuv and x-ray fluorescence; these allow one insights into the configurations populated by the interaction with the x-rays. Finally, we discover that inaccuracies in those Auger decay widths employed in previous studies have only a minor influence on ion and photon yields.
Gesehen am 24.03.2020